2019
DOI: 10.3389/fcimb.2019.00264
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification, Genotypic Diversity, Antifungal Susceptibility, and Clinical Outcomes of Infections Caused by Clinically Underrated Yeasts, Candida orthopsilosis, and Candida metapsilosis: An Iranian Multicenter Study (2014–2019)

Abstract: Despite the increasing occurrence of Candida orthopsilosis and Candida metapsilosis in clinical settings, little is known about their microbiological and clinical properties. Herein, we conducted a national retrospective study (2014–2019) from multiple centers in Iran. Among the 1,770 Candida isolates collected, we identified 600 Candida parapsilosis species complex isolates. Isolate identification was performed by 9-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…C. orthopsilosis isolates were recovered from all centers involved (n = 4) and varied in AFLP fingerprint profiles and showed a higher degree of heterogeneity that could be due to the hybrid nature of this species (Pryszcz et al, 2014). Positivity of one blood samples for both C. parapsilosis and C. orthopsilosis was extensively discussed in our previous study (Arastehfar et al, 2019a) and confirmed earlier findings (Barbedo et al, 2015) that almost 9.5% of blood isolates contained both species.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…C. orthopsilosis isolates were recovered from all centers involved (n = 4) and varied in AFLP fingerprint profiles and showed a higher degree of heterogeneity that could be due to the hybrid nature of this species (Pryszcz et al, 2014). Positivity of one blood samples for both C. parapsilosis and C. orthopsilosis was extensively discussed in our previous study (Arastehfar et al, 2019a) and confirmed earlier findings (Barbedo et al, 2015) that almost 9.5% of blood isolates contained both species.…”
Section: Discussionsupporting
confidence: 83%
“…In order to check the genotypic diversity, a previously described AFLP fingerprinting method was used (Arastehfar et al, 2019a). Diluted PCR products were analyzed by capillary electrophoresis on an ABI 3730xL Genetic Analyzer (ThermoFisher Scientific, Waltham, MA, USA) and the obtained data were analyzed by Bionumerics software v7.6.2 (Applied Math, Sint-Martens-Latem, Belgium).…”
Section: Evaluation Of Genotypic Diversity Using Aflpmentioning
confidence: 99%
“…Of note, genotypic variation weas observed for multiple FLZS isolates recovered from the same patient in this study; therefore, genotypic variation may not always be accompanied by resistance development. Interestingly, the isolate of C. orthopsilosis from the hands of a HCW may reinforce the hypothesis that, similar to C. parapsilosis, it may have been transferred from the hands of HCWs [40]. Moreover, isolation of A. melanogenum, N. albida, and N. liquefaciens from high touch areas, which are reported to have elevated MIC values to various antifungals [41][42][43] and finding Aureobasidium melanogenum in both blood and the environment are worrisome.…”
Section: Discussionmentioning
confidence: 59%
“…These differences between the observed susceptibility in the studied isolates may be due to different geographical locations and climatic conditions. In this regard, environmental conditions can affect the expression of certain genes and production of specific enzymes in fungi [29]. Furthermore, the number of isolates and diversity of the studied species can fundamentally influence the results.…”
Section: Discussionmentioning
confidence: 99%